Language poetry, psychoanalysis, and the textual production of history. Issue 1 (2nd January 2018) - Eyers, Tom
Abstract : In recent years, literary scholars have turned again to the question of literary form in its interaction with historical and political pressures. Rather than rehashing those debates, this essay demonstrates how, through close attention to poetic form, a new theorization of poetic temporality and history is possible, one that takes due account of the speculative productivity of literary language itself. 'Language poetry' by Ron Silliman and Bruce Andrews, apparently so affectless and 'out of time', is shown to be intimately concerned with the articulation of an especially collective and political vision of historical potentiality. At one and the same time, the verse discussed bars, through various formal ruses, the very vision of historical force that it otherwise announces. This push and pull between the possibility and impossibility of a specifically poetic instantiation of time and history is progressively shown to be bound up with issues central to debates in psychoanalysis, coalescing around the interpenetration of personal and collective histories and the ambiguities of the proper name.